Protecting Satellite Telecommunication by Limiting the Use of Anti-Satellite Weapons Under International Space Law - Kania Maharani; Aktieva Tri Tjitrawati; Sinar Aju Wulandari (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2025)
The increasing utilization of outer space has brought about unprecedented opportunities and potential security challenges. The development of anti-satellite (ASAT) weapons has raised concerns about the militarization of space and the potential for conflict. This research examines the legal framework governing ASAT weapons under international space law, focusing on the Outer Space Treaty (OST) and the International Telecommunication Union (ITU) Radio Regulations. It analyzes the limitations of existing legal instruments in addressing the threats posed by ASATs, particularly their potential to generate space debris and disrupt critical satellite infrastructure. This research adopts normative (doctrinal) legal methods by incorporating statutes and conceptual frameworks to analyze primary and secondary legal sources in order to investigate legal standards regarding militarization and disarmament in space. This research highlight that the current legal framework is insufficient to prevent the proliferation and use of ASAT weapons and proposes the development of a new international treaty specifically addressing ASATs. This treaty would provide clearer definitions, stricter regulations, and stronger enforcement mechanisms to ensure the long-term sustainability and security of space activities. This research also explores the role of the ITU in promoting the peaceful and responsible use of outer space through its Radio Regulations and technical expertise. The findings emphasize the need for greater cooperation between the ITU and other international organizations to address the challenges posed by ASAT weapons and ensure the continued benefits of space technology for all humankind.